Experimental and numerical investigation of high viscosity oil-based multiphase flows - Alagbe, Solomon Oluyemi (Cranfield University, 2013)
Multiphase flows are of great interest to a large variety of industries because flows of two or more immiscible liquids are encountered in a diverse range of processes and equipment. However, the advent of high viscosity oil requires more investigations to enhance good design of transportation system and forestall its inherent production difficulties. Experimental and numerical studies were conducted on water-sand, oil-water and oilwater- sand respectively in 1-in ID 5m long horizontal pipe. The densities of CYL680 and CYL1000 oils employed are 917 and 916.2kg/m3 while their viscosities are 1.830 and 3.149Pa.s @ 25oC respectively. The solid-phase concentration ranged from 2.15e-04 to 10%v/v with mean diameter of 150micron and material density of 2650kg/m3. Experimentally, the observed flow patterns are Water Assist Annular (WA-ANN), Dispersed Oil in Water (DOW/OF), Oil Plug in Water (OPW/OF) with oil film on the wall and Water Plug in Oil (WPO). These configurations were obtained through visualisation, trend and the probability density function (PDF) of pressure signals along with the statistical moments. Injection of water to assist high viscosity oil transport reduced the pressure gradient by an order of magnitude. No significant differences were found between the gradients of oil-water and oil-water-sand, however, increase in sand concentration led to increase in the pressure losses in oil-water-sand flow. Numerically, Water Assist Annular (WA-ANN), Dispersed Oil in Water (DOW/OF), Oil Plug in Water (OPW/OF) with oil film on the wall, and Water Plug in Oil (WPO) flow pattern were successfully obtained by imposing a concentric inlet condition at the inlet of the horizontal pipe coupled with a newly developed turbulent kinetic energy budget equation coded as user defined function which was hooked up to the turbulence models. These modifications aided satisfactory predictions.
Keywords: Minimum Transport Condition (MTC); Heavy oil; Water assisted flow; Core annular flow; Computational Fluid Dynamics (CFD); Probability Density Function (PDF)